Delivery of AntagomiR-7 through polymer nanoparticles for assisting B Cell to alleviate systemic lupus erythematosus - Guo, Hui; Ma, Jiangtao; Zhang, Yanli; Mao, Yan; Hu, Ziwei; Lin, Ying; Yu, Feng; Wang, Wei; Liu, Yaling (Frontiers in Bioengineering and Biotechnology, 2023)
An autoimmune condition known as systemic lupus erythematosus (SLE) is characterized by B cell hyperresponsiveness and persistent generation of pathogenic autoantibodies that cause damage to various organs and tissues. The treatments available today are either ineffective or have adverse effects. The dysregulation of B cell activation is crucial for the emergence of SLE. MiR-7 explicitly targeted PTEN mRNA in B cells. Treatment with antagomiR-7 reduced B cell hyperresponsiveness and prevented the onset of lupus. As a result, inhibiting miR-7 may be used therapeutically to treat SLE. We developed a SA (sialic acid)-poly (D, L-lactide-co-glycolide) (SA-PLGA) nano delivery system to deliver antagomiR-7 into splenic B cells since the stability and targeted delivery of miRNA remain significant challenges in vivo. Results show that SA-PLGA nanoparticles (SA-PLGA@antagomiR-7) loaded with antagomiR-7 display good biocompatibility and shield antagomiR-7 from degradation, extending the miRNA's duration in circulation in vivo. Additionally, in MRL/Ipr lupus mice, SA-PLGA@antagomiR-7 is successfully delivered to the splenic B cells and preferentially enriched in the diseased spleen in MRL/Ipr lupus mice. The SA-PLGA@antagomiR-7 NPs therapy effectively decreases immunological abnormalities, normalizes splenic B cell subtypes, and suppresses B cell activation. The antagomiR-7 NPs exhibit excellent therapeutic efficiency and high biosafety collectively, which may result in a more effective treatment for SLE.